(3QSGdI MbGFb Yde GdJhMjOs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3GdMeO ddg hGdMeO ef fYeg CeG HYO abO SCdfi HYV ef jfJei Zdi Cf GPcQ dg QSGdg eTJedI Ydi MbGFb Yde GdJhMjO s
(3BNQgG (B:s
(3bO KHJ Cf GdMQ ebUhO HGdbUO GdChd hEf cGf cd dg HbOQ hGdMeO dh GgH GdYbd hedge GdUhGH s
(3Vef eLehY , JQJjHgG (B: (3GdSGOSs
(3GdfSNI HgG MhGTs
(3GfXQg eY GdeNWhW Qbe (B259s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B- (3cdjI Mbhb (B(112 (3H(B) s
Keywords: (3GdJhMjO hGdedd hGdfMds